The Effect of Price Earning Ratio, Dividend Payout Ratio, and Debt to Equity Ratio on Firm Value in Non-Cyclical Consumer Companies - Muhammad Tsani Abdul Hakim; Depi Hasanah; Muhammad Anton Athoillah; Setia Mulyawan; Iwan Setiawan (International Journal of Nusantara Islam, 2026)
The growth in the number of sharia investors and the increase in the market capitalization of sharia stocks in Indonesia reflect a high interest in Islamic-based investments, particularly in the defensive primary consumer goods sector (non-cyclical consumer goods). Amid this trend, it is important to understand the fundamental factors that influence company value, so that investors can make more rational decisions and company management can increase their stock market value. This study aims to examine the effect of Price to Earnings Ratio (PER), Dividend Payout Ratio (DPR), and Debt to Equity Ratio (DER) on company value, proxied by Price to Book Value (PBV), in non-cyclical consumer sector companies consistently listed in the Indonesian Sharia Stock Index (ISSI) during the 2016–2020 period. The study sample consisted of 15 companies with a total of 75 panel data observations. The analysis was conducted using panel data regression with fixed effects. The results showed that DER had a significant positive effect on company value, whereas PER and DPR did not. Simultaneously, these three variables influenced company value. These results reinforce signaling theory, where a high debt structure can be perceived as an indicator of management confidence in the company's prospects. This research contributes to the growing literature on Islamic finance, focusing on strategic and stable sectors in the capital market.